Pengaruh Sari Kacang Hijau Terhadap Kenaikan Kadar HB Pada Ibu Hamil - Mayasari, Miranti; Sanjaya, Riona; Sagita, Yona Desni; Putri, Nopi Anggista (Wellness And Healthy Magazine, 2021)
According to the World Health Organization (WHO), 20% of the 515,000 maternal deaths worldwide are caused by anemia. Anemia is a condition where there is a decrease in hemoglobin, hematocrit and erythrocyte counts below normal values. Generally, anemia is a condition in which the hemoglobin and erythrocyte levels are lower than normal by setting Hb 11gr% as the basis. The research purpose was to determine the effect of giving green bean extract on the increase of HB levels in pregnant women of Seroja mother's class in Karang Rejo Village in the working area of Ketapang Public Health Center North Lampung 2021. The type of research used is pre-experimental with a one-group pre-test and post-test design approach. The population in this research were pregnant women in the third trimester. The sample in this study amounted to 15 people. The sampling technique used was purposive sampling. Univariate and Bivariate analysis used dependent t-test The results showed that the average Hb level in pregnant women of the third trimester before consuming green bean extract was 9.747, the minimum Hb level was 9.0 and the maximum was 11.0. The average Hb level in pregnant women of the their trimester after consuming green bean extract was 10,707, the minimum Hb level was 9.8 and the maximum was 12.0. There was an effect of Green Bean Extract on the Increase of HB Levels in pregnant women of the third trimester in Seroja class Karang Rejo Village, in the working area of Ketapang Public Health Center North Lampung with a p-value 0.000. The health workers can provide information about the benefits of non-pharmacological treatments such as giving green bean extract to increase hemoglobin levels to prevent anemia. Abstrak: Menurut World Health Organization (WHO) 20% dari 515.000 kematian maternal di seluruh dunia disebabkan oleh anemia. Anemia merupakan suatu keadaan adanya penurunan kadar hemoglobin, hematokrit dan jumlah ertirosit dibawah nilai normal. Anemia secara umum merupakan suatu keadaan di mana kadar hemoglobin dan eritrosit lebih rendah dari normal dengan menetapkan Hb 11gr% sebagai dasarnya. Tujuan penelitian adalah untuk Diketahui pengaruh pemberian sari kacang hijau terhadap kenaikan kadar HB pada ibu hamil di kelas ibu Seroja Desa Karang Rejo Wilayah Kerja Puskesmas Ketapang Kabupaten Lampung Utara Tahun 2021. Jenis penelitian yang digunakan adalah pre eksperimental  dengan pendekatan one group pre test and post test desaign. Populasi dalam penelitian ini adalah ibu hamil Trimester III. Sampel dalam penelitian ini berjumlah 15 orang. Tehnik sampling yang di gunakan yaitu purposive sampling. Analisa Univariat dan Bivariat menggunkan uji t dependen. Hasil penelitian didapat rata-rata kadar Hb pada ibu hamil TM III sebelum mengkonsumsi sari kacang hijau adalah 9,747, kadar Hb minimal 9,0 dan maksimal 11,0. Rata-rata kadar Hb pada ibu hamil TM III sesudah mengkonsumsi sari kacang hijauadalah 10,707, kadar Hb minimal 9,8 dan maksimal 12,0. Ada Pengaruh Pemberian Sari Kacang Hijau Terhadap Kenaikan Kadar HB pada ibu hamil TM III di Kelas Ibu Seroja Desa Karang Rejo Wilayah Kerja Puskesmas Ketapang  Kabupaten Lampung Utara  p value 0,000. Petugas kesehatan dapat memberikan informasi tentang manfaat pengobatan non farmakologi seperti sari kacang hijau untuk meningkatkan kadar hemoglobin untuk mencegah anemia.